Rasa Percaya Mahasiswa pada Polisi : Studi Eksperimen pada Tweet dengan Tagar #1Hari1Oknum - Gita Juniarti; Citra Fransisca Lestari Dano Putri; Noval Sufriyanto Talani (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Publikasi (LPPMP), 2022)
The aims of this study to conduct experimental study on student’ at Department of Communication Science, State University of Gorontalo regarding information that relate to police. Police have negative image in society’ perspective, especially on Generation Z. On Twitter, netizen criticize police with hashtag #1hari1oknum. The hashtag show news from several mass media about the nasty and cruel behavior from several police. In addition, the hashtag also an attempt by public to criticize the police on Twitter. The police institution also created Twitter account, @divhumas_polri to improve their image. This research analyzes the management of information of students who given information from @divhumas_polri account and news with the hashtag #1hari1oknum. This research use positivistic paradigm, quantitative approach, and questionnaire distribution. The amount of population was 120 students, who were divided into experimental and control groups. Furthermore, 60 students were further divided into three groups base on their academic years, 2021, 2020, and 2019. The results of this study showed that students did not have high trust towards police, especially students from experimental group who received treatment to read news with hashtag #1hari1oknum. The findings also show that students manage information through central route. They are considered critical in responding to information. As generation Z who depend on gadgets, students do not believe new information from @divhumas_polri and news with hashtag #1hari1oknum immediately. Students need supporting information from other sources, find out the information about account that spreads information, and pay attention to hashtags that used.